Perancangan dan Pengembangan Sistem Manajemen Aset Berbasis Website di SD Negeri Curug 01 Bojongsari - Haerur Ritzsal; Farizi Ilham; I Made Putra Kanayo; Aurora Faradiba (CV. Multi Kreasi Media, 2026)
SD Negeri Curug 01 Bojongsari manages a number of assets that play a vital role in supporting the teaching and learning process as well as school operations. In an effort to simplify asset management, the school has utilized a web-based asset management system. However, in its practical application, issues are still encountered during the data entry process, where the operator's account occasionally accesses asset data belonging to other schools, thereby causing data discrepancies. This condition has persisted over a long period without any permanent solution, necessitating a comprehensive update and overhaul of the existing system. The objective of this study is to build and implement a web-based digital platform to streamline the workflow of data collection, administration, and monitoring of school-owned inventory. The system development method employed is the SDLC Waterfall model, which encompasses the stages of requirement analysis, system design, implementation, and system testing. Data collection was carried out through observation, interviews, and literature reviews involving school operators and related parties. The developed system features several core functionalities, including asset data management, asset categorization, room data, asset condition management, data search, asset reporting, report exporting, and asset mutation history. The expected outcome of this research is the creation of a system that can improve the accuracy of asset data management, simplify data entry and monitoring processes, and enhance efficiency and orderliness in asset recording at SD Negeri Curug 01 Bojongsari.